Two new Trechini (Coleoptera: Carabidae) from Georgian caves, Caucasus - Maghradze, Eter; Barjadze, Shalva; Lohaj, Roman; Faille, Arnaud (Zootaxa, 2025)
During investigations of the cave fauna in Georgia, two new taxa of carabid beetles were discovered. Inotrechus usholtaensis sp. nov. from Usholta Cave and Duvalius gregoi sp. nov. from Kvedi II Cave, Racha-Lechkhumi and Kvemo Svaneti region, Georgia, are described, illustrated, and differentiated from morphologically similar species. Identification keys to the species of the genera Inotrechus and Duvalius from the Caucasus are provided.